A Comparative Analysis of Mean Percentage Scores (MPS) of Senior High School Classes - Raganit, Ariel A. (Future Science / FSH-PH Publications, 2021)
This comparative analysis on the Mean Percentage Scores (MPS) results of senior high school classes for Quarters I, II, and III was a good practice that can be emulated by educators in order to give meaning to the data. MPS is not for compilation only. It must be used for decision making in lesson delivery enhancements, learning resources utilization and school improvement plan and adjustment. The design used was descriptive research. This is a comparative analysis of the results of Quarterly Assessments of senior high school classes in a public school in Leyte with the sample of five sections determined by stratified sampling technique. Data were analyzed using Mean, standard deviation, dependent sample t-test, independent sample t-test, two-way Analysis of Variance (ANOVA) and thematic analysis of interviews of subject teachers. Descriptive study is scientific research that methodically deals with a certain region or population and characterizes an occurrence, phenomenon, or fact (Modato, 2017). Based from interviews and document analysis, extracurricular activities, socio-cultural involvements, the difficulty of learning competences, and examination schedules and the school calendar in general all had an influence on students' performance. In addition, test structures, test layout, and clear directions and instructions have an impact on test results.